Kant’s Philosophy of Moral Luck - Kahn, Samuel ca. 20./21. Jh. (Sophia, 2021)
In the modern moral luck debate, Kant is standardly taken to be the enemy of moral luck. My goal in this paper is to show that this is mistaken. The paper is divided into six sections. In the first, I show that participants in the moral luck literature take moral luck to be anathema to Kantian ethics. In the second, I explain the kind of luck I am going to focus on here: consequence luck, a species of resultant luck. In the third, I explain why philosophers have taken Kantian ethics to reject moral luck and, in particular, consequence luck. In the fourth, I explain why these philosophers are mistaken, and I set out Kant’s theoretical framework for consequence luck. In the fifth, I clarify and defend this framework, and in the sixth, I interrogate and attack it.